Peer Assessment in Writing Expository Essays: A Research on Tenth Graders of Vocational School - Supriyadi, Supriyadi (Technium Social Sciences Journal, 2021)
The present work was devoted to: (a) exploring peer assessment instruments (i.e., assessment sheets) utilized by teachers in teaching expository essay writing for tenth graders of vocational schools; (b) discussing the implementation and (c) the impact of peer assessment of the peer assessment activities. In this study, the data were from information in the peer assessment implementation. Methods of data collection involved observation, interview, and documentation. The results showed that: (a) The peer assessment instruments were in compliance with the competence standards in student assessment. (b) The implementation of expository writing teaching and learning was to find out students’ progress and outcomes; it also aimed to improve learning processes. (c) Peer assessment activities help schools enhance their learning quality and teachers in comprehending the peer assessment processes. On top of that, the assessment provides students with practical experience in assessing their peers’ works, thus boosting students’ concentration in learning. Peer assessment also measures the affective domains of students (by which it eases teachers to select appropriate teaching-learning strategies). In conclusion, the assessment on students’ social attitude fall under a good category based on the students’ average score.